Thrombin Receptor Activating Peptide (TRAP) Stimulates Mitogenesis, c-fos and PDGF-A Gene Expression in Human Vascular Smooth Muscle Cells - Kanthou, Chryso; Benzakour, Omar; Patel, Geeta; Deadman, John; Kakkar, Vijay Vir; Lupu, Florea (Thrombosis and Haemostasis, 1995)
The synthetic peptide SFLLRNPNDKYEPF, identical in sequence to the new amino-terminus of the thrombin receptor generated following cleavage by thrombin, acts as a thrombin receptor agonist/ activating peptide (TRAP). In this study, Northern blot analysis showed that cultured human vascular smooth muscle cells (HVSMC) express a thrombin receptor transcript. TRAP, in contrast to thrombin was shown to be a weak mitogen for HVSMC. A combination of TRAP and enzymatically-inactivated thrombin (PPACK-thrombin) which provides receptor occupancy, did not potentiate TRAP-induced mitogenesis, indicating that TRAP and PPACK-thrombin do not reproduce the mitogenic effect of enzymatically-active thrombin. Both thrombin and TRAP, induced the expression of c-fos and the PDGF-A gene in a pertussis toxin (PTX)-insensitive manner. Examination of thrombin and TRAP-treated cells by immunofluorescence staining followed by computer assisted image analysis revealed that thrombin and to a lesser extent TRAP induced PDGF-AA protein expression. Antibodies to PDGF-AA partially inhibited thrombin but not TRAP-induced mitogenesis in HVSMC. This study indicates that in addition to the common signalling pathways utilised by thrombin and TRAP, enzymatically-active thrombin activates other signalling pathways and hence TRAP does not mimic fully the biological effect of thrombin on HVSMC.